2019
DOI: 10.1371/journal.pone.0213247
|View full text |Cite
|
Sign up to set email alerts
|

Computational elucidation of the effects induced by music making

Abstract: Music making, in the form of free improvisations, is a common technique in music therapy, used to express one’s feelings or ideas in the non-verbal language of music. In the broader sense, arts therapies, and music therapy in particular, are used to induce therapeutic and psychosocial effects, and to help mitigate symptoms in serious and chronic diseases. They are also used to empower the wellbeing and quality of life for both healthy individuals and patients. However, much research is still required to unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…We have shown that the technology is useful in providing rigorous and significant insights and empirical probing abilities for research and therapy. The results and implications of the use of the CP for practice, research, and theory in this work, and in previous work (Sandak et al, 2015(Sandak et al, , 2019a, are summarized in the table of Figure 10 and discussed here.…”
Section: Summary and Implicationsmentioning
confidence: 63%
See 4 more Smart Citations
“…We have shown that the technology is useful in providing rigorous and significant insights and empirical probing abilities for research and therapy. The results and implications of the use of the CP for practice, research, and theory in this work, and in previous work (Sandak et al, 2015(Sandak et al, , 2019a, are summarized in the table of Figure 10 and discussed here.…”
Section: Summary and Implicationsmentioning
confidence: 63%
“…The results reported for all participants, that is, for professionals and laypersons alike, appear in Sandak et al (2019a), whereas in this work, we report on the group of lay participants alone. The improvisations carried out by professionals and laypersons expressing "negative feeling" and "ugly" were quantitatively significantly different from those expressing "positive feeling" and "beautiful."…”
Section: Study 2: Music Feeling Studymentioning
confidence: 68%
See 3 more Smart Citations